Law of connection : the science of creating ideal personal and professional relationships - Losier, Michael (London : Hodder & Mobius, 2009)
The international bestselling author of Law of Attraction returns with an inspirational new guide to creating and sustaining ideal personal and professional relationships.
Keywords: Neurolinguistic programming